Certification As a Tool in the Process of Leather Sector Globalization: Market Analysis - Gabriela ZIELINSKA (Communications of International Proceedings, 2025)
The article presents selected certifications oriented on sustainable development, i.e., Bluesign, Cradle to Cradle, Oeko-Tex, Global Recycle Standard (GRS), International Association of Natural Textiles (IVN), Leather Working Group (LWG), Content Claim Standard (CCS), Fair-trade certification, SA8000 Certification, and Worldwide Responsible Accredited Production (WRAP), employed in the leather sector to ensure high quality of produced goods while supporting the implementation of sustainable production practices. The assumptions of individual certifications and the fundamental dimension of sustainable development that they implement have been presented. In the relevant literature, there is a noticeable lack of analyses focused on assessing the impact of certification on globalization directed towards sustainable development in the leather sector. A critical analysis of this issue was conducted using SWOT approach. Based on available data, it was found that an increasing number of certifications operate in the leather sector, expand their reach, and integrate tanneries worldwide, which undoubtedly contributes to effective management of natural resources and environmental protection. Furthermore, a controlled certification process facilitates international trade. However, there may be concerns regarding the fact that leather sectors in developing countries may still face difficulties accessing certification due to the high costs associated with the certification process. The globalization process of the leather sector may also be disrupted due to increasing competition among a certifications.
Keywords: Leather sector; globalization; sustainability.